Risk Culture and COVID-19 Protective Behaviors: A Cross-Sectional Survey of Residents in China - Bi, Xuejing; Zhang, Qiao; Fan, Kaisheng; Tang, SiYu; Guan, HanWen; Gao, XueQin; Cui, Yu; Ma, Yi; Wu, QunHong; Hao, YanHua; Ning, Ning; Liu, Chaojie (Frontiers in Public Health, 2021)
Abstract The Severe Acute Respiratory Syndrome CoronaVirus type 2 (SARS-CoV-2) pandemic impacted people all over the world. Our understanding of public responses, in particular the adoption of protective behaviors, is limited. The current study aimed to determine the level of protective behaviors adopted by the residents in China and its association with cultural attributes. Protective behaviors were the primary outcome indicator, measured by a summed score of ten items (ranging from 0 to 40). The self-report tendency on the four cultural attributes (individualism, egalitarianism, fatalism, hierarchy) was rated on a seven-point Likert scale. A national cross-sectional survey was conducted online from 4th to 13th August 2020. A total of 17651 respondents returned a valid questionnaire, representing 47.9% of those who accessed the online survey. The majority (89.8%) of respondents were in the age range of 18-45 years; 47.7% were male. High levels of protective behaviors were found in 81.0 % of the respondents. They were featured by high scores in a hierarchy (Median=5) and egalitarianism (Median=5) and low scores in individualism (Median=1) and fatalism (Median=1). High levels of protective behaviors were associated higher tendency toward egalitarianism (AOR=2.90, 95% CI 2.67-3.15) and hierarchy (AOR=1.66, 95% CI 1.53-1.81) and a low tendency toward fatalism (AOR=1.79, 95% CI 1.63-1.97) and individualism (AOR=2.62, 95% CI 2.41-2.85). The cultural attributes explained 17.3% of the variations in the protective behaviors. Conclusions: The Chinese culture is featured with a high tendency of hierarchy and egalitarianism and a low tendency of individualism and fatalism, associated with the high level of protective behaviors in the public responses to COVID-19. Governmental actions and communication strategies need to adapt to the cultural characteristics of their target audience.